Quartz glass manufacturing method
By pre-treating quartz glass with a solvent like pure water to inhibit microcrystal formation, the method achieves controlled surface roughness (Ra 1.5 to 3.5 μm) on quartz glass, addressing microcrack issues and reducing operational costs in film peeling prevention.
Patent Information
- Application Number
- JP2021562679
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-04
- Filing Date
- 2020-12-02
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2040-12-02
AI Technical Summary
Existing methods for forming surface roughness on quartz glass surfaces, such as sandblasting and surface treatment with liquids, result in microcracks and uneven etching, leading to insufficient film peeling prevention and high operational costs due to the need for frequent concentration adjustments of surface treatment liquids.
A method involving pre-contact of a solvent component like pure water with the quartz glass surface before surface treatment to inhibit microcrystal formation, allowing for the formation of uniform surface roughness (Ra) between 1.5 to 3.5 μm using a surface treatment liquid.
This method enables the production of quartz glass with controlled surface roughness, reducing microcracks and operational costs by maintaining consistent surface treatment without frequent liquid concentration changes, enhancing film peeling prevention.
Smart Images

Figure 0007609076000002 
Figure 0007609076000001
Abstract
Description
[Technical Field]
[0001] The present invention relates to a method for manufacturing quartz glass in which irregularities having a desired surface roughness (Ra) are formed on the surface of the quartz glass, and in particular to a method for manufacturing quartz glass jigs such as quartz capillaries used in film formation processes such as CVD processes in semiconductor device manufacturing. [Background technology]
[0002] Due to its high purity and excellent chemical resistance, quartz glass has traditionally been used as a material for semiconductor processing, optics, laboratory equipment, decoration, and other applications. These quartz glass processed products may have various textured surfaces depending on their intended use. In particular, providing texture on the inner surface of furnace tubes used in semiconductor processing prevents peeling of polysilicon films and other materials during LPCVD (Low Pressure Chemical Vapor Deposition) processing and prevents particles from being generated during wafer heat treatment.
[0003] Known methods for textured quartz glass surfaces include sandblasting and surface treatment using a mixture of HF / CH3COOH / NH4F (surface treatment solution). Sandblasting, which involves mechanical destruction of the surface, can result in microcracks on the quartz glass surface, which can lead to particle generation and is therefore not necessarily effective. Surface textured surfaces using surface treatment solutions have long been used because they do not exhibit the microcracks described above, making them suitable for use in semiconductor processes. Furthermore, in semiconductor processes, it is generally known that a higher surface roughness reduces the likelihood of film peeling in order to prevent the polysilicon film from peeling off from the quartz glass surface (hereinafter referred to as "film peeling prevention").
[0004] However, surface treatment methods using quartz glass surface treatment solutions have problems such as surface roughness variation and difficulty in control compared to processing methods involving mechanical destruction, such as sandblasting. In particular, when quartz capillaries used in the film-forming process in semiconductor manufacturing are surface-treated with a surface treatment solution, the resulting surface roughness (Ra) is approximately 1 μm. Furthermore, in the case of surfaces with large curvatures, such as those used in the CVD process in semiconductor device manufacturing, it is thought that many microcrystals, which serve as nuclei for the formation of irregularities, tend to form, or the gaps between the microcrystals tend to become small. Therefore, from the perspective of preventing film peeling in semiconductor processes, a surface roughness (Ra) of less than 1 μm is insufficient compared to the film thickness, and is therefore insufficient in effectiveness. Therefore, a surface roughness (Ra) of approximately 1.5 to 3.5 μm is desirable as the numerical value of the irregularity to prevent film peeling.
[0005] Furthermore, as proposed in Patent Document 1 (Japanese Patent No. 4455018), it is possible to control the surface roughness (Ra) of the quartz glass surface by changing the concentration of the surface treatment solution. However, this method requires changing the concentration of the surface treatment solution each time, which increases running costs and lengthens the lead time. In other words, the surface treatment solution must be replaced to change the concentration each time surface treatment is performed, which is both cumbersome and costly.
[0006] Other techniques relating to the surface roughness (Ra) of the surface of quartz glass include Patent Documents 2 and 3 listed below. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Patent No. 4455018 [Patent Document 2] Patent No. 4437365 [Patent Document 3] Japanese Patent Application Publication No. 10-36140 Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention has been made in view of the above circumstances, and aims to provide a method for producing quartz glass that can control the surface roughness (Ra) of the irregularities on the glass surface in a relatively simple manner when forming irregularities on the surface of the quartz glass using a surface treatment liquid for surface treatment of the quartz glass. [Means for solving the problem]
[0009] As a result of extensive research into achieving the above-mentioned object, the inventors have discovered that, in forming irregularities by surface treatment with a surface treatment liquid that is free of microcracks, a surface roughness (Ra) of the surface irregularities of quartz capillaries used in semiconductor processes can be achieved in the range of 1.5 to 3.5 μm by contacting the surface of the quartz glass with a solvent component that is not involved in the liquid treatment, such as pure water, before surface treatment of the quartz glass with the surface treatment liquid, and then performing surface treatment with the surface treatment liquid before the solvent dries, thereby forming irregularities with a relatively large surface roughness on the quartz glass surface, which led to the present invention.
[0010] In the manufacturing method of the present invention, before the surface treatment of the quartz glass with a surface treatment liquid, a solvent component that is not involved in the liquid treatment, such as pure water, is brought into contact with the surface of the quartz glass, and then the surface treatment is carried out with the surface treatment liquid. The action or mechanism on the surface of the quartz glass during this process is not clear, but the following is generally assumed.
[0011] For example, when a surface treatment solution containing HF and NHF is used, etching quartz glass typically produces ammonium silicofluoride (NH4)2SiF6 (microcrystals) through a reaction between the quartz glass and the mixture. It is believed that this ammonium silicofluoride precipitates and grows as microcrystals on the surface of the quartz glass. Because the areas where microcrystals precipitate on the surface of the quartz glass hinder etching by hydrofluoric acid, the etching process slows down on parts of the quartz glass surface, resulting in uneven etching and the formation of irregularities on the quartz glass surface. Furthermore, once microcrystals precipitate, new microcrystals may precipitate, but the existing microcrystals are likely to continue growing. Once these microcrystals grow into crystals and cover the glass surface, etching is hindered across the entire glass surface, preventing any further etching differences. In contrast, in the manufacturing method of the present invention, moisture (tiny water droplets) is present on a portion of the quartz glass surface, and the surface treatment solution does not directly contact the glass surface in those areas. Therefore, microcrystals do not precipitate at this stage. Furthermore, because the amount of moisture present on the quartz glass surface is sufficiently small compared to the amount of the surface treatment solution, the moisture mixes with the surface treatment solution, and the glass surface where moisture was present eventually comes into contact with the surface treatment solution. However, there are areas on the moisture-free glass surface where microcrystals have already precipitated. Since recrystallization proceeds in areas where microcrystals have already precipitated, it is presumed that new microcrystals are unlikely to precipitate on the glass surface where moisture was present, and only HF etching proceeds. Therefore, in the present invention, the presence of moisture is thought to inhibit the formation of irregularities by the surface treatment solution during the time until the moisture mixes with the surface treatment solution, and as a result, it is thought that relatively coarse irregularities can be formed on the quartz glass surface.
[0012] Therefore, the present invention provides the following method for producing quartz glass. 1. In a method for producing quartz glass having an uneven surface by treating the surface of the quartz glass with a surface treatment liquid, a solvent component that is not involved in the surface treatment with the surface treatment liquid is brought into contact with the surface of the quartz glass in advance, and then, before the solvent component dries, Immediately after A method for producing quartz glass, characterized in that surface treatment is carried out with the above surface treatment liquid to form irregularities on the glass surface with a surface roughness (Ra) of 1.5 to 3.5 μm. 2. The method for producing quartz glass according to 1 above, wherein the solvent component not involved in the surface treatment is water or pure water. 3. A method for producing quartz glass according to 1 or 2 above, wherein the method for contacting the solvent component not involved in the surface treatment with the surface of the quartz glass is to pour the solvent component onto the surface of the quartz glass, to spray the solvent component onto the surface of the quartz glass with an atomizer, or to generate a mist of the solvent component or to contact the surface of the quartz glass with the solvent component at a humidity of 70% or more. 4. A method for producing silica glass according to any one of the above 1 to 3, wherein the component of the surface treatment liquid for silica glass is a mixed acid containing HF, NH4F, and acetic acid. 5. The method for producing silica glass according to any one of the above items 1 to 4, wherein the silica glass produced by the method is a silica glass jig used in a film formation process in semiconductor manufacturing. 6. The method for producing silica glass according to 5 above, wherein the silica glass jig is a thin silica tube having an inner diameter of 4.0 to 100.0 mm and an outer diameter of 8.0 to 106.0 mm. [Effects of the Invention]
[0013] According to the method for producing a glass surface of the present invention, in the step of forming irregularities by surface treatment with a surface treatment solution that is free of microcracks, it is possible to produce quartz glass having irregularities with a surface roughness (Ra) in the range of 1.5 to 3.5 μm, and this is a relatively simple and economical production method without the need to change the concentration of the surface treatment solution. [Brief explanation of the drawings]
[0014] [Figure 1]1 is a graph showing the surface roughness (average Ra) of the glass surface of each of the surface-treated quartz capillaries in Examples 1 to 7 and Comparative Examples 1 to 7. DETAILED DESCRIPTION OF THE INVENTION
[0015] The present invention will be described in more detail below. The present invention is a method for producing quartz glass having irregularities with a desired surface roughness (Ra) on the surface, in which the surface of the quartz glass is treated using a surface treatment liquid.
[0016] Examples of quartz glass that is not subjected to treatment to form irregularities on the surface include natural quartz and synthetic quartz, and commercially available products can be used as appropriate depending on the intended use, etc. In particular, natural quartz glass for semiconductor manufacturing processes is preferably used. For example, "HERALUX-LA" (trade name, manufactured by Shin-Etsu Quartz Co., Ltd.) and "HERALUX-E-LA" (trade name, manufactured by Shin-Etsu Quartz Co., Ltd.) can be used.
[0017] The present invention includes a step of contacting the surface of the quartz glass in advance with a solvent component that is not involved in the surface treatment with the surface treatment liquid.
[0018] The solvent components that are not involved in the surface treatment with the surface treatment liquid are solvent components that do not chemically react with the components of the surface treatment liquid described below to produce crystals, and are not particularly limited, and examples thereof include water, pure water, ethanol, etc., with water or pure water being particularly preferred.
[0019] Examples of methods for contacting the above-mentioned solvent component with the surface of the quartz glass include pouring the solvent component onto the surface of the quartz glass, spraying the solvent component with a spray bottle, or contacting the surface of the quartz glass with a mist of the solvent component or with the solvent component in a state where the humidity is 70% or higher.
[0020] The above method is sufficient as long as the solvent component is present on the surface of the target quartz glass, or the surface of the quartz glass is wet with the solvent component. Furthermore, environmental conditions such as temperature and humidity can be appropriately selected depending on the type and properties of the solvent component used so that the solvent component does not dry out. Typically, the temperature is room temperature (15-25°C), and the humidity is not particularly limited. The method of contacting the solvent component with the quartz glass surface under high humidity conditions is preferably carried out after maintaining the solvent component at a humidity of 75% or higher and room temperature (15-25°C) for 30 minutes or more.
[0021] Next, the surface of the target quartz glass is subjected to a surface treatment using a surface treatment liquid before the solvent component dries.
[0022] The surface treatment liquid may be any conventionally used liquid, and specifically, a surface treatment liquid (chemical liquid) containing hydrogen fluoride (HF) and ammonium fluoride (NH4F) is preferably used. In particular, an aqueous solution containing 10 to 50 mass% hydrogen fluoride, 6 to 30 mass% ammonium fluoride, and 30 to 60 mass% organic acid is preferably used. The organic acid is not particularly limited, but examples thereof include acetic acid, formic acid, and propionic acid. Furthermore, the liquid temperature when using the surface treatment liquid is preferably 15 to 25°C.
[0023] The method using the surface treatment solution is a conventionally known chemical treatment method known as the frost method, which processes the surface of quartz glass into a surface having fine and smooth irregularities, i.e., a surface on which fine irregularities without microcracks are formed.
[0024] In the present invention, by carrying out the above-mentioned series of steps, it is possible to obtain quartz glass having irregularities on the glass surface with a surface roughness (Ra) of 1.5 to 3.5 μm. The preferred value of the surface roughness (Ra) of the glass surface is selected appropriately depending on the intended use. For example, for quartz capillaries used in the film formation process in semiconductor manufacturing, a glass surface roughness (Ra) of 1.5 to 3.0 μm is suitable. The surface roughness (Ra) is the arithmetic mean height (Ra) defined in JIS B0601 (2001) and can be measured using commercially available measuring equipment such as a surface roughness tester.
[0025] The quartz glass having irregularities with a specific surface roughness (Ra) obtained by the above manufacturing method is useful, for example, for quartz glass jigs (tubes, furnace tubes, boats, etc.) used in film formation processes in semiconductor manufacturing, particularly for quartz thin tubes with an inner diameter of 4.0 to 100.0 mm and an outer diameter of 8.0 to 106.0 mm. [Example]
[0026] EXAMPLES The present invention will be specifically explained below with reference to examples and comparative examples, but the present invention is not limited to the following examples.
[0027] Example 1 A quartz capillary tube (commercially available as a "quartz gas supply tube") (hereinafter the same) with an outer diameter of 8 mm and an inner diameter of 4 mm, used in the film deposition process in semiconductor manufacturing, was rinsed on both the inside and outside with pure water. Pure water was sprayed on the tube with a spray bottle until the tube was immersed in a surface treatment liquid (chemical solution). The surface treatment was then performed immediately afterward. The concentrations of the surface treatment liquid were 14.9 wt% HF, 48.3 wt% acetic acid, and a liquid temperature of 22.8°C. The surface treatment was performed under these conditions. The surface roughness (Ra) of the surface-treated quartz capillary tube was measured using a Mitutoyo Corporation compact surface roughness measuring instrument, "Surftest SJ-310" (hereinafter the same). The maximum Ra was 1.92 μm, the minimum Ra was 1.56 μm, and the average Ra was 1.78 μm. This resulted in an average Ra value approximately 3.3 times higher than that of Comparative Example 1.
[0028] Example 2 A quartz capillary tube with an outer diameter of 12.7 mm and an inner diameter of 8.7 mm, which is used in the film formation process in semiconductor manufacturing, was immersed in a pure water tank, and pure water was sprayed on it using a spray bottle until just before it entered the surface treatment liquid tank. Immediately after that, surface treatment was performed using the surface treatment liquid. The concentrations of the surface treatment liquid at this time were HF concentration 14.8 wt%, acetic acid concentration 49.1 wt%, and the liquid temperature was 24.4°C. When surface treatment was performed using the surface treatment liquid under these conditions, the maximum Ra was 2.13 μm, the minimum Ra was 1.69 μm, and the average Ra was 2.01 μm, making it possible to increase the average Ra by 3.2 times compared to the state of Comparative Example 2.
[0029] Example 3 A quartz capillary tube with an outer diameter of 24.0 mm and an inner diameter of 20.0 mm, used in the film formation process in semiconductor manufacturing, was immersed in an ultrasonic cleaner filled with pure water, sprayed with pure water using a spray bottle until just before entering a surface treatment solution tank, and immediately thereafter, surface treatment was performed using the surface treatment solution. The concentrations of the surface treatment solution at this time were HF concentration 14.8 wt%, acetic acid concentration 48.4 wt%, and the solution temperature 21.3°C. When surface treatment was performed using the surface treatment solution under these conditions, the maximum Ra was 2.29 μm, the minimum Ra was 1.62 μm, and the average Ra was 1.94 μm, making it possible to increase the average Ra by approximately 3.5 times compared to the state of Comparative Example 3.
[0030] Example 4 A quartz capillary tube with an outer diameter of 106.0 mm and an inner diameter of 100.0 mm, used in the film formation process in semiconductor manufacturing, was immersed in a pure water tank containing pure water, and was sprayed with pure water using a spray bottle until just before it entered the surface treatment liquid tank. Immediately afterwards, it was subjected to surface treatment with the surface treatment liquid. The concentrations of the surface treatment liquid at this time were HF concentration 14.9 wt% and acetic acid concentration 48.3 wt%, and the liquid temperature was 23.8°C. When surface treatment was performed with the surface treatment liquid under these conditions, the maximum Ra was 1.94 μm, the minimum Ra was 1.50 μm, and the average Ra was 1.73 μm, making it possible to increase the average Ra by approximately 3.2 times compared to the state of Comparative Example 4.
[0031] Example 5 A quartz tube with an outer diameter of 282.0 mm and an inner diameter of 275.0 mm, used in the film formation process in semiconductor manufacturing, was rinsed on both the inside and outside with pure water, and then sprayed with pure water using a spray bottle until just before it was placed in a surface treatment solution tank. Immediately afterwards, the tube was subjected to surface treatment with the surface treatment solution. The concentrations of the surface treatment solution at this time were HF concentration 14.8 wt% and acetic acid concentration 48.4 wt%, and the solution temperature was 21.3°C. When surface treatment was performed with the surface treatment solution under these conditions, the maximum Ra was 2.86 μm, the minimum Ra was 1.46 μm, and the average Ra was 2.12 μm, making it possible to increase the average Ra by approximately 1.6 times compared to the state of Comparative Example 5.
[0032] Example 6 A quartz tube with an outer diameter of 434.0 mm and an inner diameter of 422.0 mm, used in the film formation process in semiconductor manufacturing, was rinsed on both the inside and outside with pure water, and pure water was sprayed on it with a spray bottle just before it was placed in a surface treatment solution tank. Immediately after that, surface treatment was performed with the surface treatment solution. The concentrations of the surface treatment solution at this time were HF concentration 14.8 wt% and acetic acid concentration 48.4 wt%, and the solution temperature was 21.3°C. When surface treatment was performed with the surface treatment solution under these conditions, the maximum Ra was 3.54 μm, the minimum Ra was 1.97 μm, and the average Ra was 2.47 μm, making it possible to increase the average Ra by approximately 1.5 times compared to the state of Comparative Example 6.
[0033] Example 7 A quartz capillary tube with an outer diameter of 12.7 mm and an inner diameter of 8.7 mm, used in the film formation process in semiconductor manufacturing, was stored in a container humidified with pure water using a humidifier and held for 30 minutes at a temperature of 22.5°C and a humidity of 70-75% (high humidity) inside the container. The tube was then removed from the high-humidity container and subjected to surface treatment using a surface treatment solution. The concentrations of the surface treatment solution at this time were HF concentration 14.5 wt%, acetic acid concentration 48.8 wt%, and the solution temperature 20.3°C. When surface treatment was performed using the surface treatment solution under these conditions, the maximum Ra was 2.34 μm, the minimum Ra was 2.01 μm, and the average Ra was 2.17 μm, making it possible to increase the average Ra by approximately 3.4 times compared to the state of Comparative Example 7.
[0034] Comparative Example 1 A quartz capillary tube with an outer diameter of 8 mm and an inner diameter of 4 mm, which is used in the film deposition process in semiconductor manufacturing, was thoroughly dried and then subjected to a surface treatment using a surface treatment solution. The concentrations of the surface treatment solution at this time were HF concentration 14.7 wt%, acetic acid concentration 48.5 wt%, and the solution temperature was 22.0°C. When surface treatment was performed using the surface treatment solution under these conditions, the maximum Ra was 0.69 μm, the minimum Ra was 0.34 μm, and the average Ra was 0.54 μm.
[0035] Comparative Example 2 A quartz capillary tube with an outer diameter of 12.7 mm and an inner diameter of 8.7 mm, which is used in the film deposition process in semiconductor manufacturing, was thoroughly dried and then subjected to a surface treatment using a surface treatment solution. The concentrations of the surface treatment solution at this time were HF concentration 14.8 wt%, acetic acid concentration 48.3 wt%, and the solution temperature was 23.2°C. When surface treatment was performed using the surface treatment solution under these conditions, the maximum Ra was 1.27 μm, the minimum Ra was 0.38 μm, and the average Ra was 0.65 μm.
[0036] Comparative Example 3 A quartz capillary tube with an outer diameter of 24.0 mm and an inner diameter of 20.0 mm, which is used in the film deposition process in semiconductor manufacturing, was thoroughly dried and then subjected to a surface treatment using a surface treatment solution. The concentrations of the surface treatment solution at this time were HF concentration 14.9 wt%, acetic acid concentration 48.5 wt%, and the solution temperature was 21.3°C. When surface treatment was performed using the surface treatment solution under these conditions, the maximum Ra was 1.03 μm, the minimum Ra was 0.38 μm, and the average Ra was 0.56 μm.
[0037] Comparative Example 4 A quartz capillary tube with an outer diameter of 106.0 mm and an inner diameter of 100.0 mm, which is used in the film deposition process in semiconductor manufacturing, was thoroughly dried and then subjected to a surface treatment using a surface treatment solution. The concentrations of the surface treatment solution at this time were HF concentration 14.8 wt%, acetic acid concentration 48.4 wt%, and the solution temperature was 21.3°C. When surface treatment was performed using the surface treatment solution under these conditions, the maximum Ra was 0.89 μm, the minimum Ra was 0.35 μm, and the average Ra was 0.55 μm.
[0038] Comparative Example 5 A quartz tube with an outer diameter of 282.0 mm and an inner diameter of 275.0 mm, which is used in the film deposition process in semiconductor manufacturing, was thoroughly dried and then subjected to a surface treatment using a surface treatment solution. The concentrations of the surface treatment solution at this time were HF concentration 14.9 wt%, acetic acid concentration 48.5 wt%, and the solution temperature was 21.3°C. When surface treatment was performed using the surface treatment solution under these conditions, the maximum Ra was 1.96 μm, the minimum Ra was 0.52 μm, and the average Ra was 1.30 μm.
[0039] Comparative Example 6 A quartz tube with an outer diameter of 434.0 mm and an inner diameter of 422.0 mm, which is used in the film deposition process in semiconductor manufacturing, was thoroughly dried and then subjected to a surface treatment using a surface treatment solution. The concentrations of the surface treatment solution at this time were HF concentration 14.9 wt%, acetic acid concentration 48.5 wt%, and the solution temperature was 21.3°C. When surface treatment was performed using the surface treatment solution under these conditions, the maximum Ra was 2.76 μm, the minimum Ra was 0.50 μm, and the average Ra was 1.61 μm.
[0040] Comparative Example 7 A quartz capillary tube with an outer diameter of 12.7 mm and an inner diameter of 8.7 mm, which is used in the film deposition process in semiconductor manufacturing, was thoroughly dried in an environment with a room temperature of 21.3°C and a humidity of 50-60%, and then surface-treated with a surface treatment solution. The concentrations of the surface treatment solution at this time were HF concentration 14.5 wt%, acetic acid concentration 48.7 wt%, and the solution temperature was 20.5°C. When surface treatment was performed with the surface treatment solution under these conditions, the maximum Ra was 1.31 μm, the minimum Ra was 0.31 μm, and the average Ra was 0.63 μm.
[0041] The respective condition values for Examples 1 to 7 and Comparative Examples 1 to 7 are summarized in the following Table 1. Also, a graph showing the surface roughness (Ra) of the quartz capillaries surface-treated in Examples 1 to 7 and Comparative Examples 1 to 7 is shown in Figure 1.
[0042] [Table 1]
Claims
1. A method for producing quartz glass having irregularities on its surface by subjecting the surface of the quartz glass to a surface treatment using a surface treatment liquid, the method comprising the steps of: bringing a solvent component that is not involved in the surface treatment with the surface treatment liquid into contact with the surface of the quartz glass in advance; and then immediately thereafter, before the solvent component has dried, performing surface treatment with the surface treatment liquid, thereby forming irregularities on the glass surface with a surface roughness (Ra) of 1.5 to 3.5 μm.
2. 2. The method for producing quartz glass according to claim 1, wherein the solvent component not involved in the surface treatment is water or pure water.
3. 3. The method for producing quartz glass according to claim 1 or 2, wherein the method for contacting the solvent component not involved in the surface treatment with the surface of the quartz glass is a method of pouring the solvent component onto the surface of the quartz glass, a method of spraying the solvent component with a spray bottle, or a method of contacting the surface of the quartz glass with a mist of the solvent component or with the humidity of the solvent component being 70% or higher.
4. The method for producing quartz glass according to any one of claims 1 to 3, wherein the component of the surface treatment liquid for the quartz glass is a mixed acid containing HF, NH4F and acetic acid.
5. The method for producing silica glass according to any one of claims 1 to 4, wherein the silica glass produced by the above production method is a silica glass jig used in a film formation process in semiconductor manufacturing.
6. 6. The method for producing quartz glass according to claim 5, wherein the quartz glass jig is a quartz capillary having an inner diameter of 4.0 to 100.0 mm and an outer diameter of 8.0 to 106.0 mm.
Citation Information
Patent Citations
Liquid for treating surface of silica glass jig and treatment with the same
JP1998036140A
Optoelectric device manufacturing method and manufacturing device apparatus
JP2001210615A
Quartz glass lamp tube and laser excitation / amplification unit
JP2005001923A
Method of manufacturing semiconductor device
JP2005191163A
Method for manufacturing mask blank substrate, method for manufacturing substrate having multilayer film, method for manufacturing mask blank, and method for manufacturing transfer mask
JP2016145927A